THE ROLE OF TEACHERS AS CURRICULUM DEVELOPERS IN IMPROVING THE QUALITY OF LEARNING - Rizki Bobi Baihaki; Siti Mala Nurfayisa (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This paper examines in detail the importance of teacher involvement in curriculum design (CDC) and assesses its impact on improving the quality of teaching and learning. Curriculum is defined as a fundamental component of education, providing the guidance and structure necessary for student progress. The role of teachers, once considered merely implementers, has evolved into that of instructional designers, with crucial knowledge and skills to influence students' learning experiences and curriculum implementation across diverse classroom contexts. This analysis draws on a critical literature review and conceptual synthesis of research on teachers' professional roles and the Participatory Curriculum Development (PCD) process. The research emphasizes that teacher involvement, particularly during implementation and evaluation, is crucial for fostering continuous improvement and flexibility in education systems. Effective involvement, often supported by curriculum-focused professional learning, significantly enhances teacher capabilities, enabling the successful implementation of high-quality teaching practices, such as effective science discussions. Despite ongoing challenges, including the need to integrate modern concepts such as digital technologies and the Sustainable Development Goals (SDGs), strategic teacher participation ensures the curriculum remains relevant and responsive, ultimately improving overall student learning outcomes